The Influence of Work-Life Balance and Organizational Support on Organizational Citizenship Behavior: Moderated by Burnout - Arafat, Faisal Putra; Syahroni, Bachrudin; Mahadianto, Moh. Yudi (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the effects of work-life balance (WLB) and perceived organizational support (POS) on organizational citizenship behavior (OCB), with burnout as a moderating variable. Using a quantitative cross-sectional design, data were collected through a questionnaire survey of 150 service-sector employees in Jakarta, Bekasi, and Tangerang and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that WLB and POS have significant positive effects on OCB, whereas burnout has a significant negative effect. Burnout also significantly weakens the positive effects of WLB and POS on OCB, indicating that employees are less likely to engage in extra-role behavior when they experience higher levels of exhaustion. The model demonstrates strong explanatory power (R² = 0.842). These findings suggest that organizations should strengthen work-life balance practices, enhance organizational support, and implement structured burnout prevention strategies to sustain employees’ extra-role behavior.